Cross-training: A misnomer - Hawley, J. (Sportscience)
On cross-training, which is when an athlete undertakes training in a discipline other than their main sport for the sole purpose of enhancing performance in their main sport. This form of training became popular in the 1980's with the emergence of the sport of triathlon, and has been widely recommended in recent years as a technique for retaining training adaptations, and even improving performance.